Mycobacterium avium paratuberculosis in Italy: Commensal or emerging human pathogen? - Pistone, Dario; Marone, Piero; Pajoro, Massimo; Fabbi, Massimo; Vicari, Nadia; Daffara, Silvio; Dalla Valle, Claudia; Gabba, Silvia; Sassera, Davide; Verri, Annalisa; Montagna, Matteo; Epis, Sara; et al. (Digestive and liver disease, 2012)
Specific bacterial infections or alterations of the gut microbiota likely trigger immuno-pathological phenomena associated with Crohn's disease and ulcerative colitis. Mycobacterium avium subspecies paratuberculosis is a candidate etiological agent of Crohn's disease. Definitive causal connection between Mycobacterium avium subspecies paratuberculosis infection and Crohn's disease has not been demonstrated. To determine the circulation of Mycobacterium avium subspecies paratuberculosis in Crohn's disease patients and water supplies in an Italian region where this bacterium is endemic in cattle farms. Mycobacterium avium subspecies paratuberculosis screening was performed on biopsies from human patients, and from water samples, using two different PCR procedures. In hospitals where multiple specimens were obtained from different sites in the intestine, the prevalence of Mycobacterium avium subspecies paratuberculosis infection was 82.1% and 40% respectively in Crohn's disease and ulcerative colitis patients; in another hospital, where single specimens were obtained from patients, the bacterium was not detected. Control subjects also harboured Mycobacterium avium subspecies paratuberculosis, but at a lower prevalence. Tap water samples collected in the study area contained Mycobacterium avium subspecies paratuberculosis DNA. The results of screenings for Mycobacterium avium subspecies paratuberculosis in humans are deeply influenced by both the number and location of the collected biopsies. There is a wide circulation of the organism in the study area, considering the prevalence in humans and its presence in drinking water.